Obstetric-associated lower urinary tract injuries: A case series from a tertiary centre in a low-resource setting - Shantel Naicker; Thinagrin D. Naidoo; Jagidesa Moodley (Elsevier, 2020)
Obstetric-associated lower urinary tract injuries may occur during vaginal and abdominal deliveries. If these injuries go unrecognised, these patients may suffer both physical and psychosocial complications. We describe the management of 19 patients with such injuries, including their demographic profile, associated factors, and complications at a tertiary institution in a retrospective case series over a 5-year period. Bladder injuries were the most common (89.5%), mostly occurring during emergency caesarean delivery, with previous caesarean delivery and adhesions being risk factors. A primary repair was attempted at the referring institution in 35.7% of cases. Repair at the tertiary institution was mostly performed by consultants (42.9%). Early recognition and primary repair are found to reduce further complications.